Acceptance of Vehicle Automation: Effects of Demographic Traits, Technology Experience and Media Exposure. (November 2019) - Lee, Chaiwoo; Seppelt, Bobbie; Reimer, Bryan; Mehler, Bruce; Coughlin, Joseph F.
Transportation users are increasingly aware of a possible future where they may ride in or share the road with automated vehicles. However, even with recent technological advances, many are still hesitant to accept automated driving. This study explores effects of the following characteristics on acceptance: demographics including age, gender, level of education and income; experiences with technology in general, as well as technology in drivers' current vehicles; and media exposure. Survey responses from 3505 adults in the United States indicate that younger age, a high level of education, positive affect for advanced driver assistance systems currently in use, and high self-rated early technology adoption tendency have significant influence on acceptance. Data reflecting time course and salience of media coverage on knowledge and attitudes, especially with high-profile events such as a fatal crash, is presented with implications around the need for balanced media reporting with more focus on the safety benefits.